(untitled) (Research, Society and Development, 2021)
Introduction: Approaching the humanization of emergency services assistance is a necessary challenge. Patients who require hospital emergency assistance as well as healthcare professionals who work there, are under stress and tension. Objective: understand the meaning of humanization for the nursing staff in the context of urgency and emergency. Methods: Qualitative study, with a phenomenological approach in which 06 professionals from nursing staff participated. The collection of information took place in 2019 through a semi-structured interview. Results: the phenomenological concepts of “being with” and “being in the world”, made it possible to unveil the meanings of humanization for these professionals, resulting in three themes: Being there in the encounter with the other in the world of care; work process in the world of (lack of) care; elements that interfere with humanization. Conclusion: Understanding the meaning of humanization instigates reflections and changes in the world of care, nursing professionals relate, in their daily lives, with the surrounding world and the world itself, thus, it is in constant transformation and so gives meaning to care in urgent and emergency services.